Improving Junior High School Student’s Mathematical Understanding Ability using Discovery Learning Model on Relation and Function Material - Rusmawan, Rusmawan; Putra, Harry Dwi; Hendriana, Heris ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2024)
The ability of students' mathematical understanding is one of the aspects needed by students in learning mathematics. With the ability to understand mathematics will make it easier for students to solve problems because students will be able to relate and solve these problems with the concepts they have understood. This study aims to see the improvement of the mathematical understanding ability of junior high school students using a discovery learning model on Relation and Function material. The type of this research is Classroom Action Research with the research sample being all grade VIII students in one of the junior high schools in West Bandung. This study consists of 2 cycles where each cycle consists of planning, action and implementation, observation and reflection stages, with before and after the study given 2 test instrument in the form of a description. In each cycle there is an activity observation sheet. Meanwhile, to analyze the data, it is seen from the test results provided, then all data and data results are processed using SPSS software. The results of this study showed that there was an increase in the completeness of learning scenarios for teachers by 92.31% and for students by 81.25%. In addition, the results of filling out the tests given each cycle showed good results with the number of students who scored above the minimum completeness criteria in cycle I by 73.08% and cycle II by 81.88%, meaning an increase of 8.8%. Based on this, it is expected that educators can apply the Discovery Learning Model with good planning and implementation so that student learning outcomes on relation and function material can increase.